Fungal and bacterial metabolites in commercial poultry feed from Nigeria - Ezekiel, C.N.; Bandyopadhyay, Ranajit; Sulyok, M.; Warth, B.; Krska, R. (Informa UK Limited, 2012)
Metabolites of toxigenic fungi and bacteria occur as natural contaminants (e.g. mycotoxins) in feedstuffs making them unsafe to animals. The multi-toxin profiles in 58 commercial poultry feed samples collected from 19 districts in 17 states of Nigeria were determined by LC/ESI–MS/MS with a single extraction step and no clean-up. Sixtythree (56 fungal and seven bacterial) metabolites were detected with concentrations ranging up to 10,200 mgkg-1 in the case of aurofusarin. Fusarium toxins were the most prevalent group of fungal metabolites, whereas valinomycin occurred in more than 50% of the samples. Twelve non-regulatory fungal and seven bacterial metabolites detected and quantified in this study have never been reported previously in naturally contaminated stored grains or finished feed. Among the regulatory toxins in poultry feed, aflatoxin concentrations in 62% of samples were above 20 mgkg 1, demonstrating high prevalence of unsafe levels of aflatoxins in Nigeria. Deoxynivalenol concentrations exceeded 1000 mgkg 1 in 10.3% of samples. Actions are required to reduce the consequences from regulatory mycotoxins and understand the risks of the single or co-occurrence of nonregulatory metabolites for the benefit of the poultry industry.